Imbalanced lysine to arginine ratios reduced performance in juvenile cobia (Rachycentron canadum) fed high plant protein diets. (10th June 2013) - Van, M.; Rønnestad, I.; Buttle, L.; Van, H.; Espe, M.
Abstract Cobia (8.4 ± 0.1 g body weight) were fed to satiation with three test diets of high plant protein‐based ingredients and different lysine to arginine ratios, and one commercial diet (currently used for cobia rearing in Vietnam as a control for growth) for 6 weeks. The test diets contained 206 g marine ingredients kg−1, including fishmeal, krill meal and fish protein concentrate (in order of high to low inclusion), while the rest of the dietary protein was a blend of soya and pea protein concentrate, wheat protein and sunflower meal. Crystalline lysine and arginine were added in the test diets to produce either a balanced lysine to arginine ratio (BL/A; 1.1) and a high or low lysine to arginine ratio (HL/A; 1.8 and LL/A; 0.8, respectively). There were no significant differences in final body weight, weight gain, feed conversion ratio or protein gain between cobia fed BL/A‐ and commercial control diet (CCT). Cobia fed BL/A diet performed better than fish fed either HL/A‐ or LL/A diet. This was partly due to a higher feed intake and protein and lipid gain in cobia fed BL/A diet as compared to HL/A‐ and LL/A diet.